PENERAPAN KONSEP SUSTAINABLE FINANCE: Model Analitycal Hierarchy Process - Setiyowati, Harlis; Trisnawati, Luh Putu Puji (POLITEKNIK LP3I JAKARTA, 2023)
The idea of sustainable finance has gained acceptance on a global and regional scale, including in Indonesia. Applications of this new financial idea face challenges. Making a model for sustainable finance implementation is the aim of this study. The AHP model's goal is to establish a economic, social, and value environment and corporate governance. The first level is a factor, namely obstacles to the implementation of sustainable finance, namely; economic, social and environmental aspects, issues of rules and regulations, disclosure of sustainable reports and technological interventions. Based on the results of testing the AHP model, the most important factor in implementing the concept of Sustainable Finance is the